On the expediency of making double-pulse lasers for laser thermonuclear fusion - Shcherbakov, V.A. (Вопросы атомной науки и техники, 2003)
The paper demonstrates the expediency of development of double-pulse lasers for studying the thermonuclear laser target performance based on moderate fuel pre-compression and subsequent ignition of the center by the focusing shock wave.